Daily Profiles of Neuropeptides, Catecholamines, and Neurotransmitter Receptors in the Chicken Pineal Gland - Adamska, Iwona; Malz, Monika; Lewczuk, Bogdan; Blügental, Natalia; Markowska, Magdalena Aleksandra; Meronka, Robert; Majewski, Paweł Marek (Frontiers in Physiology, 2019)
The avian pineal gland is one of three equivalent central biological clocks that contain all the components of a circadian system: a photoreceptive input, oscillator, and rhythmically secreted melatonin (MEL) as an effector. The biosynthesis of MEL is regulated by the neurotransmitters noradrenaline (NE), vasoactive intestinal peptide (VIP), and pituitary adenylate cyclase-activating polypeptide (PACAP). The aim of the present study was to characterize the daily profile of neurotransmitters and their receptors in the pineal gland of male Hy-Line chickens housed under controlled light (12:12 light:dark) conditions. The pineal glands were isolated from 16-day-old birds every 2 h over a 24-h period, immediately after decapitation. The catecholamine content was measured using HPLC with electrochemical detection, whereas expression of VIP and PACAP was measured using quantitative real-time PCR (RT-qPCR) assays and Western blotting. Expression of the neurotransmitter receptors was also measured using RT-qPCR. We found daily changes in NE content, with elevated nocturnal levels, whereas the NE receptor was expressed in antiphase. Although we did not observe daily changes in VIP and PACAP protein levels, we found prominent diurnal changes in the expression of the Vip and Pacap genes. We also detected precursors of NE, 3,4-dihydroxy-L-phenylalanine (DOPA), and dopamine (DA) in the pineal glands, in addition to the DA metabolites. Our results provide the first evidence that the pineal gland itself may synthetize the neurotransmitters needed to regulate MEL biosynthesis.